A prospective cohort study examining medical and social factors associated with engagement in life activities following total hip replacement. Issue 7 (July 2017) - MacKay, C.; Webster, F.; Venkataramanan, V.; Bytautas, J.; Perruccio, A.V.; Wong, R.; Carlesso, L.; Davis, A.M.
Summary: Objectives: Studies show limited improvement in the frequency of engaging in life activities after joint replacement. However, there is a paucity of research that has examined factors, including other life events, which influence engagement following total hip replacement (THR). This research sought to identify factors associated with engaging in life activities following THR. Methods: A prospective cohort study was conducted with 376 people who had a THR for osteoarthritis (OA). Data were collected pre-surgery and 1 year post-surgery. The primary outcome was change in frequency in engagement in life activities (Late Life Disability Index (LLDI): higher scores indicate higher frequency of engagement (range 0–80)). Analyses included multivariable regression. Factors considered included: positive/negative life events, a new comorbidity, another joint replacement and complications post-surgery. Results: Participants' mean age was 64 years; 46% were male. 68% of participants had at least one comorbidity pre-surgery; 36% reported at least one new comorbidity after surgery. The mean change in LLDI frequency was an increase of 6.29 (±8.10). 36% reported one or more positive impact life events in the year following surgery; 63% reported one or more negative life events. The number of positive life events (beta = 1.24; 95% CI: 0.49, 1.99) was significantly associated with change in LLDI frequency after adjusting for age, sex, education, body mass index (BMI), comorbidities pre-surgery, number of symptomatic joints and pre-surgery pain and function, LLDI limitations and depression. Conclusions: These findings highlight the significant influence of social factors and life circumstances on engagement in life activities following THR.